Team Games Tournament Method Improves Islamic Education Learning Outcomes: Metode Turnamen Permainan Tim Meningkatkan Hasil Pembelajaran Pendidikan Islam - Mutaqin, Muh. Kunta Akmalal; Istikomah, Istikomah (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Education quality is strongly influenced by the teaching methods applied, as they shape students’ understanding and engagement. Specific Background: In Islamic Religious Education and Character Education at SDN Grogol 2 Kediri, conventional methods such as lectures and assignments have led to low student comprehension. Knowledge Gap: Limited studies have explored the application of the Team Games Tournament (TGT) cooperative learning model in early grade Islamic education using a classroom action research (CAR) framework. Aims: This study aimed to investigate the application of the TGT model to improve learning outcomes in grade II Islamic Religious Education. Results: Conducted over two CAR cycles involving 30 students, findings showed an increase in the average score from 69.33 (cycle I) with 40% not meeting the minimum criteria, to 77.46 (cycle II) with only 3% not meeting the criteria. Novelty: The research uniquely integrates TGT with structured digital game-based tournaments for Islamic education in early grades. Implications: These results suggest that TGT can serve as an effective and engaging pedagogical approach to improve student performance and participation in Islamic Religious Education at the elementary level. Highlights: Improved scores from cycle I to cycle II through TGT model Integration of digital games in Islamic Religious Education learning Active participation and reduced number of students below minimum criteria Keywords: Cooperative Learning, Team Games Tour, Islamic Education, Learning Outcomes, Elementary School